2015
DOI: 10.1186/s12904-015-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a hospice rapid response service on preferred place of death, and costs

Abstract: BackgroundMany people with a terminal illness would prefer to die at home. A new palliative rapid response service (RRS) provided by a large hospice provider in South East England was evaluated (2010) to provide evidence of impact on achieving preferred place of death and costs. The RRS was delivered by a team of trained health care assistants and available 24/7. The purpose of this study was to (i) compare the characteristics of RRS users and non-users, (ii) explore differences in the proportions of users and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Existing evidence suggests that provision of a rapid response service increases the chances of patients dying at home if that is their preference as does increased public awareness of the HAH services. [17][18][19] The final NAHH standard promotes systems and processes to ensure pre/post-bereavement support for patients (where appropriate), carers and families. Views on enablers from respondents to the survey identified that services benefited from a well-trained and extensive network of third sector support, volunteers and family support.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence suggests that provision of a rapid response service increases the chances of patients dying at home if that is their preference as does increased public awareness of the HAH services. [17][18][19] The final NAHH standard promotes systems and processes to ensure pre/post-bereavement support for patients (where appropriate), carers and families. Views on enablers from respondents to the survey identified that services benefited from a well-trained and extensive network of third sector support, volunteers and family support.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,38 Although direct evidence on the monitoring of marketing and referral strategies of hospice at home services was far from explicit, it was recommended by Gage et al that commissioners would benefit from knowing about service under-utilisation. 48 In addition, Wilson et al noted that carers required more awareness raising about the availability of bereavement support. 49…”
Section: "Marketing and Referral"mentioning
confidence: 99%
“…Gage et al suggests that having an integrated co-ordinating service between providers did not impact upon whole systems costs. 48 "Service Responsiveness and Availability"…”
Section: "Sustainable Funding Model"mentioning
confidence: 99%
See 1 more Smart Citation
“…Physician support, palliative care involvement, and family support improve congruence [ 8 10 ]. The use of 24/7 services increased the chance of dying at a preferred place by 2.1 times [ 11 ]. The services of home-based end-of-life care, as part of palliative care programs, increased the probability of care and dying at home [ 12 ].…”
Section: Introductionmentioning
confidence: 99%